2016
DOI: 10.1080/02786826.2016.1167833
|View full text |Cite
|
Sign up to set email alerts
|

Filtration performances of HVAC filters for PM10 and microbial aerosols— Influence of management in a lab-scale air handling unit

Abstract: Filtration performances of air handling unit (AHU) filters for particles and microbial aerosols were investigated. The influence of the AHU operational conditions on the behavior of microorganisms collected on the filters was also studied. A lab-scale AHU with two filtration stages was developed and validated for the study of downsized filters with industrial geometries. Three types of filters of different efficiency were considered: G4, F7, and F9, according to European standard EN 779. Two configurations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…The micronized rice particles were intended to be representative of outdoor PM 10 in terms of size distribution but not with regard to chemical or biological composition. The initial concentration of Penicillium chrysogenum was 2250±850 CFU per gram of micronized rice particles . Note that Penicillium chrysogenum was the only fungus found in the rice sample.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The micronized rice particles were intended to be representative of outdoor PM 10 in terms of size distribution but not with regard to chemical or biological composition. The initial concentration of Penicillium chrysogenum was 2250±850 CFU per gram of micronized rice particles . Note that Penicillium chrysogenum was the only fungus found in the rice sample.…”
Section: Methodsmentioning
confidence: 92%
“…With the same air velocity during a filter clogging and release test, the fungal fraction released was between 0.009% and 0.33%. González et al . also studied the microbial release from a two‐stage filtration process.…”
Section: Introductionmentioning
confidence: 99%
“…It is made of fiberglass felt. The median fiber diameter is 1 ± 0.2 lm (González et al 2016). The nominal filtration velocity recommended by the manufacturer is 0.2 m s -1 .…”
Section: Characteristics Of the Filter Mediamentioning
confidence: 99%
“…The filter F7 efficiency was between 91 and 99%. With reference to the study of the efficiency curves of the filtration carried out by González et al (2016), the F7 showed efficiency between 80 and 90% for particle diameters equal to 0.4 lm, and it increased with particle diameters \ 0.4 lm. Comparing the present virus size, the experimental setup shows consistent filtration performance.…”
Section: Detection and Quantification Of Adenovirus Upstream Downstrmentioning
confidence: 99%
“…The filtration velocity is 0.2 m s -1 and the median fiber diameter is 1 ± 0.2 lm. In this study, a circular filter of 17.72 cm 2 was used in each output (González et al 2016). The experimental design consists of a vertical column made of polymethyl methacrylate where the viruses will be generated and homogenized in the upward air flow.…”
Section: Characteristics Of the Filter Mediummentioning
confidence: 99%